Development and quality assessment of functional probiotic yoghurt drink from sweet cream buttermilk - Chapagain, Kshiteej; Karki, Tika Bahadur; Ojha, Pravin (Journal of Food Science and Technology Nepal, 2014)
A new functional yoghurt drink consisting of banana and honey was developed from Sweet Cream Buttermilk (SCBM)and its physicochemical, microbiological and sensory characteristics were assessed with respect to plain and skim milk yoghurt drinks. Storage stability of drinks prepared by using standard probiotic culture of lactobacillus acidophilus (La5) was determined in terms of acidity, strain viability and consumer acceptability of final products. In corporation of banana and honey decreased post acidification and increased the carbohydrate (13.15-13.37%), proteins (2.23-2.25%) and ash content (0.53%). It was observed that the total solid content was increased from 5.72±0.17 % in plain yoghurt drink (PYD) to 16.39±0.07% in skim milk based drink (SYD) and 16.38±0.04% in buttermilk based drink (BYD). Greater count of probiotic cells was observed in Buttermilk based yoghurt drink (5.9*108 CFU/ml) than in Skim milk based yoghurt drink (1.4*108 CFU/ml) at the end of 30 days of refrigerated storage. Fifty percent of the consumer preferred refrigerated Buttermilk based yoghurt drink for 27 days. DOI: http://dx.doi.org/10.3126/jfstn.v8i0.11750 J. Food Sci. Technol. Nepal, Vol. 8 (52-59), 2013